O koncepcii razvitija detsko-junošeskogo sporta v Rossijskoj Federacii - Seyranov, S. G.; Bulgakova, N. Zh.; Evseev, S. P. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The article examines the main provisions of the concept of the development of youth sports in the Russian Federation and, in particular, the concepts: school sports, out-of-school sports, student sports and "ministry of sports" sports, presented at the Scientific and Practical Conference on Improving the Management Model of Children and Youth Sports, held by the Public Chamber of the Russian Federation on September 15, 2020.